The Coverage of Classroom Management in Teacher Evaluation Rubrics. (May 2019) - Gilmour, Allison F.; Majeika, Caitlyn E.; Sheaffer, Amanda W.; Wehby, Joseph H.
Many teachers struggle with the classroom management skills necessary to support students with disabilities. Teacher evaluation is a potential method for supporting teachers' use of classroom management strategies. The authors evaluate the extent to which classroom management was included in state teacher evaluation rubrics and the types of classroom management topics that were included in the rubrics. They find that while one fifth of standards and indicators were related to classroom management, there was large variability across states. Rubrics that included classroom management focused on proactive strategies, but often did not include specific evidence-based practices that could help teachers improve their classroom management skills. Very few rubrics included any focus on how to address student misbehavior. In light of these findings, the authors provide a discussion of the importance of including high-quality standards and indicators about classroom management to support teachers of students with disabilities.